Fate of hydroxyapatite nanoparticles during dynamic in vitro gastrointestinal digestion: the impact of milk as a matrix. Issue 6 (8th March 2021) - Choki, Kinley; Li, Siqi; Ye, Aiqian; Jameson, Geoffrey B.; Singh, Harjinder
Abstract : The dissolution behavior and the structural changes of nHA during dynamic gastric digestion and intestinal digestion were examined. Milk formed a structural clot and significantly retarded the dissolution of nHA during gastric digestion. Abstract : This study investigated the behavior of nano-sized particles of hydroxyapatite (nHA) during dynamic in vitro gastrointestinal digestion, alone or dispersed within skim milk. The dissolution and the structural changes of nHA were investigated by analyzing the dissolution of calcium and using transmission electron microscopy and X-ray diffraction. The dissolution of nHA during gastric digestion involved a rapid early stage and a much slower later stage. It was incomplete by the end of gastric digestion, both with and without milk. However, there was no sign of nHA recrystallization in the intestinal phase. X-ray diffraction analysis of digesta showed the breakdown of the crystalline structure of nHA and the formation of potentially new calcium phosphate phases during digestion. Skim milk formed a structural clot and significantly retarded the dissolution of nHA during gastric digestion. Possible mechanisms leading to the incomplete dissolution of nHA and the matrix effect of milk are discussed.